Validation of the acceptability of 10x20 mm specimens for fracture toughness determination of high-strength steels: - Walters, C.L.; Voormeeren, L.O.; Janssen, M.; Wallin, K. (2013)
Standards have traditionally required that fracture toughness specimens be the full thickness of the base material. However, this requirement may be unnecessary, especially if minimum specimen size dimensions based on plastic zone are met and the subsized specimens are statistically adjusted for the size effect. The current paper presents the results for full-thickness proportional Single Edge Notched Bending (SENB) specimens according to BS7448-1 that are 25 mm by 50 mm in crosssection and then compares these results to specimens of the same material that are 10 mm by 20 mm in cross section. The result is that for a temperature near the lower portion of the transition curve (-60°C to -70°C), the subsize specimens are in very good agreement. These results hold for two different loading rates. After correction for statistical size effect, the fracture toughnesses of the subsize specimens are within 10% of the full-size specimens. This is conservative. The difference is attributed to the statistical nature of fracture in the transition region.